NON-STATE HIGHER EDUCATIONAL INSTITUTIONS FUNDING SOURCES AND FORMATION - Yuldashev Khushnidbek Soyibjon ugli (American Journals, 2025)
This article analyzes the sources of financial resources of non-state higher education institutions and their placement mechanisms. The development process of private higher education institutions in the world and in Uzbekistan, sources of financing, and their role in the economy are considered. Non-state higher education institutions in Uzbekistan have determined ways of forming their funds mainly through student payment-contract revenues, private investors' contributions, international grants and loans, state benefits, and corporate cooperation. Proposals have been made to improve the use of funds to ensure the financial stability of non-state educational institutions and increase their efficiency.
Keywords: Non-state higher educational institutions, financial resources, investment, grants, placement of funds, material and technical base, education policy of Uzbekistan.